2021
DOI: 10.1590/s2175-97902020000418954
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antiproliferative and antioxidant attributes of ethanolic extract of resinous sediment from Etlingera elatior (Jack.) inflorescence

Abstract: The ethanolic extract of resinous sediment (EERS) of Etlingera elatior young inflorescence was examined for its anticancer effect and potential antioxidant activity. The anticancer effect of the EERS was evaluated on four human cancer cell lines, HCT 116, HT-29, Hela, and MCF-7, using the MTT assay. GC-MS analysis showed that the main components found in the EERS were nonyl cyclopropane (4.44%), 1-tetradecane (3.66%), cyclotetradecane (2.41%), cyclododecane (1.92%), and 1-decene (1.72%). The antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In a previous study carried out by Parra et al (2018) demonstrated the antioxidant capacity of the aerial parts the ethanolic extract of S. nutans (ABT 0.01301 mM TE/g and FRAP 0.02765 mM TE/g). This indicates that its polyphenolic components are reducing agents (electron donors) or metal chelators (Al-Mansoub et al, 2021), with the ability to eliminate hydroxyl radicals, superoxide anion, and others (Zhang et al, 2019). There is a significant relationship between antioxidant activity and total polyphenol content, specifically between TPC/DPPH and TPC/ABTS, as there is a 96.57% and 79.53% linear relationship, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study carried out by Parra et al (2018) demonstrated the antioxidant capacity of the aerial parts the ethanolic extract of S. nutans (ABT 0.01301 mM TE/g and FRAP 0.02765 mM TE/g). This indicates that its polyphenolic components are reducing agents (electron donors) or metal chelators (Al-Mansoub et al, 2021), with the ability to eliminate hydroxyl radicals, superoxide anion, and others (Zhang et al, 2019). There is a significant relationship between antioxidant activity and total polyphenol content, specifically between TPC/DPPH and TPC/ABTS, as there is a 96.57% and 79.53% linear relationship, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This finding shows that torch ginger extract could be used as a skin cancer chemopreventive or chemotherapeutic drug. Moreover, the anticancer activity of the torch ginger inflorescence was examined by Al-Mansoub et al (2021) in four human cancer cell lines: HCT 116, HT-29, Hela, and MCF-7. The human colorectal adenocarcinoma cell line HT-29 was susceptible to the extraction potential selective cytotoxicity.…”
Section: Antitumormentioning
confidence: 99%
“…The plants containing abundant phenols and flavonoid compounds are a probable source of natural antioxidants. The ability of phenolic compounds to act as reducing agents, electron donors, oxygen quenchers, or metal chelators is mainly attributable to their redox characteristics (Al-Mansoub et al, 2021). The antioxidant activity of A. ciliata Bunge (PAB) was reported by Zhang et al (2019).…”
Section: Antioxidant Capacitymentioning
confidence: 99%